Harnessing Agroforestry as an Anticipatory Climate Change Adaptation and Regenerative Agriculture Practice - Cabriole, Marie Aislinn; Gonsalves, Julian (CGIAR System Organization, 2024)
Harnessing agroforestry as an anticipatory climate change adaptation strategy offers a regenerative approach to agriculture, building resilience within vulnerable farming systems. The International Institute of Rural Reconstruction (IIRR) drives this effort through its work in climate-smart villages, where climate-resilient practices are implemented to prepare agri-food systems for future climate impacts. Key to this approach is anticipatory adaptation, where interventions are designed proactively to address projected climate challenges before they manifest. In collaboration with CGIAR's ClimBeR Initiative (Building Systemic Resilience against Climate Variability and Extremes), IIRR is capturing the significant contributions of smallholder farmers to resilient, sustainable food systems. This partnership highlights local, evidence-based solutions, emphasizing the role of community-driven adaptation in promoting climate resilience. Through agroforestry and other climate-smart practices, IIRR’s efforts underscor